Modification of ZnO Nanowires Induced by Ion Irradiation for Device Applications (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
ZnO nanowires grown by hydrothermal method were exposed to a beam of 50 keV argon ions at a fluence of \(1× 10^{16}\) ions/cm\(^{2}\). The surface morphology of the nanowires has been investigated using high resolution electron microscopy. Raman scattering study has been carried out, which shows specific features resulting from argon ion irradiation. The post-irradiated nanowires exhibit high degree of surface roughness of dimension about few nm and tip of each nanowire is sharpened after this irradiation. The combined effect of surface roughening and tip sharpening are expected to enhance the aspect ratio as well as the effective surface-to-volume ratio. We invoked size and curvature dependent sputtering and defect dynamics to explain the observed features. We envisage that such increase of surface area and tip sharpening may enhance applications of these modified ZnO nanowires in the field of catalysis, gas sensing, field emission and photovoltaic.
Keywords: Nanowire; Ion irradiation; Surface modification; HRTEM